Quick-charge type lithium ion battery and preparation method thereof
By granulating lithium iron phosphate and using lithium titanium phosphate nanowire surface modification, combined with fast-charging graphite, high-porosity separator and silicone electrolyte, the problem of poor charging and discharging performance and rate performance of lithium-ion batteries is solved, and a lithium-ion battery with high-risk performance and low battery impedance is achieved.
Patent Information
- Application Number
- CN202510020396.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The charging and discharging performance and rate performance of existing lithium-ion batteries are poor, and cannot meet the future market demand for the charging speed of lithium-ion batteries.
Granulated lithium iron phosphate was prepared by granulating lithium iron phosphate, and the positive electrode sheet was surface modified by spraying using lithium titanium phosphate nanowires, combined with fast-charge graphite and high-porosity single-sided coating membrane and silicone electrolyte.
It has achieved high-rate performance, low battery impedance and excellent fast charging capabilities of lithium-ion batteries, meeting the future market demand for lithium-ion battery charging speed.
Smart Images

Figure CN119864485A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a fast-charging lithium-ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in various fields due to their advantages such as light weight, high energy density, no memory effect, long cycle life and environmental friendliness. With the development of the times, people have higher requirements for the fast charging performance of lithium-ion batteries. The American Society of Automotive Engineers believes that compared with internal combustion engine vehicles, the limited driving range and long charging time of electric vehicles (EVs) will cause drivers' range anxiety and create obstacles to the development of potential users. Therefore, the U.S. Department of Energy has identified extremely fast charging (XFC) as a key challenge to ensure the large-scale adoption of electric vehicles.
[0003] The internal structure of a lithium-ion battery consists of four parts: negative electrode material, electrolyte, separator and positive electrode material. Most of the negative electrode materials of existing lithium-ion batteries use graphite materials, and most of the positive electrode materials use lithium-containing compounds. Existing lithium-ion batteries have poor charging and discharging performance and rate performance, and cannot meet the future market demand for lithium-ion battery charging speed. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a fast-charging lithium-ion battery and a preparation method thereof, which solves the technical problems of poor charge and discharge performance and rate performance of the prior lithium-ion battery.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a fast-charging lithium-ion battery, comprising the following steps:
[0009] S1. Preparation of positive electrode
[0010] Granulating lithium iron phosphate to obtain granulated lithium iron phosphate, using the granulated lithium iron phosphate to prepare positive electrode slurry; preparing the positive electrode slurry into a pole piece; surface treating at least one side of the pole piece with lithium titanium phosphate nanowires to obtain a positive electrode piece;
[0011] S2. Preparation of negative electrode sheet
[0012] Selecting fast-charging graphite to prepare negative electrode slurry, and making the negative electrode slurry into a negative electrode sheet;
[0013] S3. Preparation of fast-chargeable lithium-ion batteries
[0014] The separator, the positive electrode sheet and the negative electrode sheet are made into a winding core, the coating surface of the separator faces the positive electrode sheet, and an organic silicon electrolyte is injected into the winding core to prepare a fast-charging lithium-ion battery.
[0015] Lithium iron phosphate is granulated to prepare granulated lithium iron phosphate. The morphology of granulated lithium iron phosphate is that a number of small lithium iron phosphate particles are attached to large lithium iron phosphate particles. On the one hand, granulated lithium iron phosphate only needs to use carbon black as a conductive agent, and carbon black can be evenly mixed between large and small particles to achieve better conductive contact; on the other hand, the granulated lithium iron phosphate particles can form a contact between a large lithium iron phosphate particle and a plurality of small lithium iron phosphate particles, which is more conducive to the transmission and diffusion of lithium ions; thirdly, the granulated lithium iron phosphate particles can better absorb and store electrolyte after being made into electrodes.
[0016] Using a single-sided coated diaphragm and silicone electrolyte, with the diaphragm coating facing the positive electrode, can ensure good adhesion between the diaphragm and the positive electrode, improve ionic conductivity, and reduce battery impedance; the silicone electrolyte has high ionic conductivity, good thermal stability, excellent SEI film-forming performance, and high voltage and high rate performance.
[0017] Preferably, the method for preparing the positive electrode sheet comprises the following steps:
[0018] (1) mixing the granulated lithium iron phosphate, carbon black, PVDF and solvent in a certain weight ratio to prepare a positive electrode slurry;
[0019] (2) coating, baking and rolling the positive electrode slurry in sequence to obtain a pole piece;
[0020] (3) Mix lithium titanium phosphate nanowires and organic glue in a mass ratio of 1:(20-100), add the mixture into a sprayer, set the speed of the electrode plate passing through the sprayer gun to 0.8-1.5 m / min, set the spray pressure of the sprayer to 0.1-0.8 MPa, and set the spraying range to the electrode plate coating width. Perform surface treatment on the electrode plate to obtain a positive electrode plate.
[0021] The positive electrode is prepared by using lithium titanium phosphate nanowires to modify the surface of the electrode through a spraying process. By spraying lithium titanium phosphate nanowires on the surface of the electrode, the contact and coating effect between lithium titanium phosphate and the active material particles on the surface of the electrode are enhanced. The nanowires of lithium titanium phosphate are wound to form a loose structure through the spraying process, which can increase the fit between the positive electrode and the diaphragm, and also increase the liquid absorption and retention effect of the positive electrode, eliminate polarization, and improve the rate performance. Since lithium titanium phosphate and lithium iron phosphate have the same crystal form, they have a synergistic effect in increasing the electronic conductivity of the positive electrode material and the transmission rate of lithium ions; and the nanowire structure of lithium titanium phosphate has a small diameter, which reduces the diffusion distance of lithium ions when in close contact with the active material particles on the surface of the electrode, thereby increasing the diffusion rate of lithium ions.
[0022] Preferably, the preparation method satisfies at least one of the following conditions:
[0023] The amount of lithium iron phosphate used in the granulation is 95-99 parts, the amount of carbon black is 1-4 parts, and the amount of PVDF is 1-4 parts;
[0024] The preparation method of granulated lithium iron phosphate comprises secondary sintering large lithium iron phosphate particles with a particle size distribution D50 of 0.2 to 2 μm and small lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm at 350 to 500° C. for 3 to 6 hours;
[0025] The mass ratio of the lithium iron phosphate particles with a D50 of 0.2 to 2 μm to the lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm is 1:(3 to 20);
[0026] The coating method comprises coating the positive electrode slurry on the positive electrode current collector, and controlling the double-sided coating surface density to be 350-420 g / m 2 ;
[0027] The organic gum is selected from at least one of gelatin, carrageenan, xanthan gum and agar.
[0028] Preferably, the solvent is NMP, and the preparation method of the positive electrode slurry comprises dissolving the PVDF in NMP, vacuum stirring for 3 to 6 hours, and obtaining a PVDF glue with a mass fraction of 3% to 8%; mixing the granulated lithium iron phosphate and carbon black for dry mixing for 0.5 to 2 hours, and then adding the PVDF glue, and vacuum stirring for 4 to 6 hours; finally, adding an appropriate amount of NMP according to the viscosity of the slurry, vacuum stirring for 0.5 to 1.5 hours, and then vacuum standing for defoaming for 0.5 to 2 hours to obtain the positive electrode slurry.
[0029] Preferably, the method for preparing the negative electrode sheet comprises the following steps:
[0030] (1) slurrying fast-charging graphite, carbon black, lithiated CMC, modified SBR and deionized water to prepare negative electrode slurry;
[0031] (2) The negative electrode slurry is sequentially coated, baked, rolled, and cut to obtain a negative electrode sheet.
[0032] The negative electrode slurry is prepared using fast-charging graphite. Since the fast-charging graphite has smaller grain size, lower degree of graphitization, and smaller crystal orientation, it has more advantages in rate performance, volume expansion, and preventing electrode rebound.
[0033] Preferably, the preparation method satisfies at least one of the following conditions:
[0034] The fast-filling graphite is used in an amount of 95 to 99 parts, the carbon black is used in an amount of 0.5 to 1.5 parts, the lithium CMC is used in an amount of 0.8 to 2 parts, and the modified SBR is used in an amount of 1 to 2.5 parts;
[0035] The fast-filling graphite is artificial graphite with a particle size distribution D50 of 6 to 11 μm and a specific surface area of 1.3 to 4 m 2 / g, the degree of graphitization is 93.8% to 94.2%, and the OI value is 2.8 to 3.2;
[0036] The coating method comprises coating the negative electrode slurry on the negative electrode current collector, and controlling the double-sided coating surface density to be 180-230 g / m 2 .
[0037] Preferably, the preparation method of the negative electrode slurry comprises dissolving the lithiated CMC in deionized water, vacuum stirring for 4 to 6 hours, and obtaining a CMC glue solution with a mass fraction of 0.8% to 1.8%; mixing the fast-filling graphite and carbon black for dry mixing for 1.5 to 2.5 hours, and then adding the CMC glue solution, vacuum stirring for 3 to 6 hours; continuing to add the SBR, vacuum stirring at a low speed for 0.5 to 1.5 hours; finally, adding deionized water according to the viscosity of the slurry, vacuum stirring for 0.5 to 1.5 hours, and then vacuum standing for defoaming for 0.5 to 2 hours to obtain the negative electrode slurry.
[0038] Preferably, the diaphragm is a PTFE diaphragm with a porosity of 45% to 55%, a single-side coating of aluminum oxide and PVDF, and a thickness of 12+3 μm.
[0039] Preferably, the preparation method satisfies at least one of the following conditions:
[0040] The composition of the organosilicon electrolyte is 1.2M LiPF6 / EC:DMC (1:1 in vol.), and the incorporation ratio of polysiloxane oligomer is 10% to 30%;
[0041] The method for preparing a fast-charging lithium-ion battery also includes: subjecting the core to sequential steps of baking, hot pressing, ultrasonic welding, top and side sealing, baking, liquid injection, standing, pressure forming, aging, exhaust and secondary sealing, and capacity separation.
[0042] In a second aspect, the present invention provides a fast-charging lithium-ion battery prepared by the preparation method described in the first aspect, wherein the fast-charging lithium-ion battery has a 4C constant current charging ratio of 95.0%-99.0%, a 6C constant current charging ratio of 95.0%-97.0%, an 8C constant current charging ratio of 92.0%-94.0%, and a capacity retention rate of 97%-99% after 500 6C / 1C fast charging cycles.
[0043] (III) Beneficial effects
[0044] The present invention provides a fast-chargeable lithium-ion battery and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The preparation method of the fast-charging lithium-ion battery of the present invention includes granulating lithium iron phosphate to prepare granulated lithium iron phosphate. The morphology of the granulated lithium iron phosphate is that a number of small lithium iron phosphate particles are attached to large lithium iron phosphate particles. On the one hand, the granulated lithium iron phosphate only needs to use carbon black as a conductive agent, and the carbon black can be evenly mixed between large and small particles to achieve better conductive contact; on the other hand, the granulated lithium iron phosphate particles can form a contact between a large lithium iron phosphate particle and a plurality of small lithium iron phosphate particles, which is more conducive to the transmission and diffusion of lithium ions; thirdly, the granulated lithium iron phosphate particles can better absorb and store electrolyte after being made into pole pieces.
[0046] 2. The preparation method of the fast-charge lithium-ion battery of the present invention includes using lithium titanium phosphate nanowires to modify the surface of the pole piece through a spraying process to prepare a positive pole piece. By spraying lithium titanium phosphate nanowires on the surface of the pole piece, the contact and coating effect between lithium titanium phosphate and the active material particles of the pole piece surface, lithium iron phosphate, is enhanced. The nanowires of lithium titanium phosphate are wound to form a loose structure through the spraying process, which can increase the fit between the positive pole piece and the diaphragm, and also increase the liquid absorption and retention effect of the positive pole piece, eliminate polarization, and improve the rate performance. Since lithium titanium phosphate and lithium iron phosphate have the same crystal form, the two have a synergistic effect in increasing the electronic conductivity of the positive electrode material and the transmission rate of lithium ions; and the nanowire structure of lithium titanium phosphate has a small diameter, and when it is in close contact with the active material particles on the pole piece surface, it reduces the diffusion distance of lithium ions and increases the diffusion rate of lithium ions.
[0047] 3. The preparation method of the fast-charging lithium-ion battery of the present invention includes using fast-charging graphite to prepare negative electrode slurry. Since the fast-charging graphite has a smaller grain size, a lower degree of graphitization, and a smaller degree of crystal orientation, it has more advantages in rate performance, volume expansion, and preventing electrode rebound.
[0048] 4. The preparation method of the fast-charging lithium-ion battery of the present invention includes using a high-porosity single-sided coated diaphragm and an organosilicon electrolyte. The coated surface of the diaphragm faces the positive electrode, which can ensure that the diaphragm and the positive electrode sheet have good adhesion, and the high porosity of the diaphragm can more effectively promote the absorption and penetration of the electrolyte by the diaphragm, improve the ionic conductivity, and reduce the impedance of the battery; the organosilicon electrolyte has high ionic conductivity, good thermal stability, excellent SEI film-forming performance and high voltage and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 Schematic diagram of the surface treatment device for the positive electrode sheet prepared in Example 1;
[0051] 1-heater; 2-spray powder; 3-angle control valve; 4-wind shield;
[0052] Figure 2 Planar SEM of the positive electrode sheet prepared in Example 1;
[0053] Figure 3 This is a cross-sectional SEM of the positive electrode sheet prepared in Example 1;
[0054] Figure 4 The cyclic voltammetry curve (CV curve) of the positive electrode sheet prepared in Example 1;
[0055] Figure 5 This is an XRD comparison diagram of the negative electrode fast-filling graphite and conventional graphite in Example 1. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0058] Example 1
[0059] The present embodiment provides a fast-charging lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte. The positive electrode sheet includes the following raw materials in parts by weight: 97.2 parts of granulated lithium iron phosphate, 1 part of conductive carbon black, and 1.8 parts of PVDF copolymer; the negative electrode sheet includes the following raw materials in parts by weight: 96.5 parts of fast-charging graphite, 0.7 parts of conductive carbon black, 1 part of lithiated CMC, and 1.8 parts of modified SBR; the diaphragm is a PTFE diaphragm with a porosity of 48% and a single-sided alumina and PVDF coating and a thickness of 12+3μm; the electrolyte is 1.2M LiPF6 / EC:DMC (1:1 in vol.), and the incorporation ratio of polysiloxane oligomer is 15%.
[0060] A method for preparing a fast-charging lithium-ion battery comprises the following steps:
[0061] S1. Preparation of positive electrode
[0062] The said amount of PVDF is dissolved in NMP, and the mixture is stirred in vacuum for 4 hours to obtain a PVDF glue solution with a mass fraction of 5%; the said amount of granulated lithium iron phosphate and conductive carbon black are mixed and dry-blended for 1 hour, and then the PVDF glue solution is added thereto, and the mixture is stirred in vacuum for 4.5 hours; finally, an appropriate amount of NMP is added according to the viscosity of the slurry, and the mixture is stirred in vacuum for 1 hour and then allowed to stand in vacuum for defoaming for 1 hour to obtain the positive electrode slurry.
[0063] The preparation process of granulated lithium iron phosphate is to prepare large lithium iron phosphate particles with a D50 of 0.2 to 2 μm and small lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm by secondary sintering at 425°C for 5 hours, wherein the mass ratio of lithium iron phosphate particles with a D50 of 0.2 to 2 μm to lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm is 1:3.
[0064] The positive electrode slurry prepared above was coated on the positive electrode current collector ((15+1+1) μm double-sided carbon-coated aluminum foil), and the double-sided coating surface density was controlled at 380 g / m 2 , after baking and rolling, a large rolled pole piece is obtained;
[0065] like Figure 1 , mix lithium titanium phosphate nanowires and carrageenan particles in a mass ratio of 1:50 and add them to the feeding port of the thermal spray machine, turn on the electrode conveying roller and set the speed through the thermal spray machine gun to 1.0m / min, turn on the compressed air and heater switch of the thermal spray machine at the same time, adjust the pressure value to 0.6MPa, the heating temperature to 140℃, adjust the angle control valve to set the spraying range to the electrode coating width setting, and wait until all the large rolled electrode sheets pass through the thermal spray machine gun to complete the treatment of one side of the large rolled electrode sheet, and repeat the above operation to treat the other side of the electrode sheet. After the surface treatment, the large rolled electrode sheet is cut into positive electrode sheets. The planar SEM of the prepared positive electrode sheet is as follows Figure 2 , cross-sectional SEM Figure 3 The cyclic voltammetry curve (CV curve) of the prepared positive electrode sheet is as follows Figure 4 .
[0066] S2. Preparation of negative electrode sheet
[0067] The amount of lithiated CMC is dissolved in deionized water, and the mixture is stirred in vacuum for 4 hours to obtain a CMC slurry with a mass fraction of 1.2%; the amount of graphite and conductive carbon black are mixed and dry-blended for 1.8 hours, and then the CMC slurry is added thereto, and the mixture is stirred in vacuum for 4 hours; the amount of SBR is continued to be added, and the mixture is stirred in vacuum at a low speed for 1 hour; finally, an appropriate amount of deionized water is added according to the viscosity of the slurry, and the mixture is stirred in vacuum for 1 hour, and then allowed to stand in vacuum for defoaming for 1.2 hours to obtain the negative electrode slurry.
[0068] The negative electrode slurry prepared above was coated on the negative electrode current collector (6 μm copper foil), and the double-sided coating surface density was controlled at 200 g / m 2 , the large rolled electrode sheet is baked, rolled and cut into negative electrode sheets;
[0069] S3. Battery assembly
[0070] The positive and negative electrode sheets and diaphragms are made into a roll core according to a winding structure, wherein the single-sided coated side of the diaphragm faces the positive electrode sheet, the diaphragm is a PTFE diaphragm with a porosity of 45%, and is coated with alumina and PVDF on one side with a thickness of 12+3μm. The roll core is prepared into a lithium-ion battery through the processes of baking, hot pressing, ultrasonic welding, top and side sealing, baking, liquid injection, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0071] Example 2
[0072] The present embodiment provides a fast-charging lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte. The positive electrode sheet includes the following raw materials in parts by weight: 96.5 parts of granulated lithium iron phosphate, 1.5 parts of conductive carbon black, and 2 parts of PVDF copolymer; the negative electrode sheet includes the following raw materials in parts by weight of fast-charging graphite: 96 parts of fast-charging graphite, 1 part of conductive carbon black, 1 part of lithiated CMC, and 2 parts of modified SBR; the diaphragm is a PTFE diaphragm with a porosity of 52% and a single-sided alumina and PVDF coating and a thickness of 12+3μm; the electrolyte is 1.2M LiPF6 / EC:DMC (1:1 in vol.), and the incorporation ratio of polysiloxane oligomers is 20%.
[0073] A method for preparing a fast-charging lithium-ion battery comprises the following steps:
[0074] S1. Preparation of positive electrode
[0075] (1) The amount of PVDF is dissolved in NMP and vacuum stirred for 5 hours to obtain a PVDF glue solution with a mass fraction of 6%; the amount of granulated lithium iron phosphate and conductive carbon black are mixed and dry-mixed for 2 hours, and then the PVDF glue solution is added thereto and vacuum stirred for 5 hours; finally, an appropriate amount of NMP is added according to the viscosity of the slurry, and the mixture is vacuum stirred for 0.7 hours and then vacuum-stirred for 1.5 hours to defoam to obtain the positive electrode slurry.
[0076] The preparation process of granulated lithium iron phosphate is to prepare large particles with a D50 of 0.2 to 2 μm and small particles with a D50 of 0.02 to 0.1 μm by secondary sintering at 375°C for 3 hours, wherein the mass ratio of lithium iron phosphate particles with a D50 of 0.2 to 2 μm to lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm is 1:15.
[0077] (2) The positive electrode slurry prepared above was coated on the positive electrode current collector ((15+1+1) μm double-sided carbon-coated aluminum foil), and the double-sided coating surface density was controlled at 400 g / m 2 , after baking and rolling, a large rolled pole piece is obtained;
[0078] (3) Mix lithium titanium phosphate nanowires and xanthan gum particles in a mass ratio of 1:30 and add them to the feeding port of the thermal sprayer. Turn on the electrode conveying roller and set the speed through the thermal sprayer gun to 1.2m / min. At the same time, turn on the thermal sprayer compressed air and heater switches, adjust the pressure value to 0.8MPa, and the heating temperature to 180°C. Adjust the angle control valve to set the spray range to the electrode coating width setting. When all the large rolled electrode sheets pass through the thermal sprayer gun, the treatment of one side of the large rolled electrode sheet is completed. Repeat the above operation to treat the other side of the electrode sheet. After the surface treatment, the large rolled electrode sheet is cut into positive electrode sheets.
[0079] S2. Preparation of negative electrode sheet
[0080] (1) The amount of lithiated CMC is dissolved in deionized water, and the mixture is stirred in vacuum for 5 hours to obtain a CMC slurry with a mass fraction of 1.5%; the amount of graphite and conductive carbon black are mixed and dry-blended for 2.2 hours, and then the CMC slurry is added thereto, and the mixture is stirred in vacuum for 4.5 hours; the amount of SBR is continued to be added, and the mixture is stirred in vacuum at a low speed for 1.2 hours; finally, an appropriate amount of deionized water is added according to the viscosity of the slurry, and the mixture is stirred in vacuum for 0.8 hours, and then the mixture is allowed to stand in vacuum for defoaming for 1.5 hours to obtain the negative electrode slurry.
[0081] (2) The negative electrode slurry prepared above was coated on the negative electrode current collector (6 μm copper foil), and the double-sided coating surface density was controlled at 210 g / m 2 , the large rolled electrode sheet is baked, rolled and cut into negative electrode sheets;
[0082] S3. Battery assembly
[0083] The positive and negative electrode sheets and diaphragms are made into a roll core according to a winding structure, wherein the single-sided coated side of the diaphragm faces the positive electrode sheet, the diaphragm is a PTFE diaphragm with a porosity of 50%, and is coated with alumina and PVDF on one side with a thickness of 12+3μm. The roll core is prepared into a lithium-ion battery through the processes of baking, hot pressing, ultrasonic welding, top and side sealing, baking, liquid injection, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0084] Example 3
[0085] The present embodiment provides a fast-charging lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte. The positive electrode sheet includes the following raw materials in parts by weight: 98 parts of granulated lithium iron phosphate, 0.8 parts of conductive carbon black, and 1.2 parts of PVDF copolymer; the negative electrode sheet includes the following raw materials in parts by weight: 97 parts of fast-charging graphite, 0.5 parts of conductive carbon black, 1.1 parts of lithiated CMC, and 1.4 parts of modified SBR; the diaphragm is a PTFE diaphragm with a porosity of 45%, a single-sided alumina and PVDF coating, and a thickness of 12+3μm; the electrolyte is 1.2M LiPF6 / EC:DMC (1:1 in vol.), and the incorporation ratio of polysiloxane oligomer is 25%.
[0086] A method for preparing a fast-charging lithium-ion battery comprises the following steps:
[0087] S1. Preparation of positive electrode
[0088] (1) The amount of PVDF is dissolved in NMP and vacuum stirred for 4.5 hours to obtain a PVDF glue solution with a mass fraction of 4%; the amount of granulated lithium iron phosphate and conductive carbon black are mixed and dry-mixed for 1.5 hours, and then the PVDF glue solution is added thereto and vacuum stirred for 6 hours; finally, an appropriate amount of NMP is added according to the viscosity of the slurry, and the mixture is vacuum stirred for 1.2 hours and then vacuum-stirred for 1.8 hours to defoam to obtain the positive electrode slurry.
[0089] The preparation process of granulated lithium iron phosphate is to prepare large particles with a D50 of 0.2 to 2 μm and small particles with a D50 of 0.02 to 0.1 μm by secondary sintering at 475°C for 6 hours, wherein the mass ratio of lithium iron phosphate particles with a D50 of 0.2 to 2 μm to lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm is 1:20.
[0090] (2) The positive electrode slurry prepared above was coated on the positive electrode current collector ((15+1+1) μm double-sided carbon-coated aluminum foil), and the double-sided coating surface density was controlled to be 415 g / m 2 , after baking and rolling, a large rolled pole piece is obtained;
[0091] (3) Mix lithium titanium phosphate nanowires and agar particles at a mass ratio of 1:75 and add them to the feeding port of the thermal sprayer. Turn on the electrode conveying roller and set the speed of passing through the thermal sprayer gun to 1.5m / min. At the same time, turn on the compressed air and heater switch of the thermal sprayer, adjust the pressure to 0.3MPa, the heating temperature to 120℃, adjust the angle control valve to set the spray range to the electrode coating width setting, and wait until the large rolled electrode has passed through the thermal sprayer gun to complete the treatment of one side of the large rolled electrode. Repeat the above operation to treat the other side of the electrode. After the surface treatment, the large rolled electrode is cut into positive electrodes.
[0092] S2. Preparation of negative electrode sheet
[0093] (1) The amount of lithiated CMC is dissolved in deionized water, and the mixture is stirred in vacuum for 5.5 hours to obtain a CMC slurry with a mass fraction of 1.8%; the amount of graphite and conductive carbon black are mixed and dry-blended for 2.5 hours, and then the CMC slurry is added thereto, and the mixture is stirred in vacuum for 5 hours; the amount of SBR is continued to be added, and the mixture is stirred in vacuum at a low speed for 0.8 hours; finally, an appropriate amount of deionized water is added according to the viscosity of the slurry, and the mixture is stirred in vacuum for 1.2 hours, and then the mixture is allowed to stand in vacuum for defoaming for 1.8 hours to obtain the negative electrode slurry.
[0094] (2) The negative electrode slurry prepared above was coated on the negative electrode current collector (6 μm copper foil), and the double-sided coating density was controlled at 220 g / m 2 , the large rolled electrode sheet is baked, rolled and cut into negative electrode sheets;
[0095] S3. Battery assembly
[0096] The positive and negative electrode sheets and diaphragms are made into a roll core according to a winding structure, wherein the single-sided coating of the diaphragm faces the positive electrode sheet, the diaphragm is a PTFE diaphragm with a porosity of 55%, and is coated with alumina and PVDF on one side with a thickness of 12+3μm. The roll core is prepared into a lithium-ion battery through the processes of baking, hot pressing, ultrasonic welding, top and side sealing, baking, liquid injection, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that the granulated lithium iron phosphate in Example 1 is replaced by ungranulated lithium iron phosphate particles with a particle size distribution D50 of 0.2 to 2 μm, and the rest is the same as Example 1.
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 1 is that, in the method for preparing a fast-charging lithium-ion battery, lithium titanium phosphate nanowires are not included when preparing the positive electrode sheet, and the rest is the same as Example 1.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 1 is that conventional graphite is used to replace the fast-filling graphite in Example 1, and the rest is the same as Example 1. The XRD comparison diagram of the fast-filling graphite and the conventional graphite is shown in Figure 5 .
[0103] Comparative Example 4
[0104] The difference between this comparative example and Example 1 is that a diaphragm with a porosity of 30% is used to replace the diaphragm in Example 1, and the other aspects are the same as Example 1.
[0105] Comparative Example 5
[0106] The difference between this comparative example and Example 1 is that lithium iron phosphate electrolyte is used to replace the electrolyte in Example 1, and the rest is the same as Example 1.
[0107] Comparative Example 6
[0108] The difference between this comparative example and Example 1 is that in the preparation method of the fast-charging lithium-ion battery, when preparing the positive electrode, lithium titanium phosphate nanowires and carrageenan particles are mixed in a mass ratio of 1:50 and then coated on the active layer surface of the electrode to replace the spraying process of Example 1, and the rest is the same as Example 1.
[0109] Depend on Figure 2 It is known that after Figure 1 The positive electrode prepared by the device shown in the figure is subjected to surface treatment on the electrode, and the lithium titanium phosphate nanowires uniformly coat the active lithium iron phosphate particles on the surface of the electrode, and the coating is in a loose state, which can effectively improve the rate performance; Figure 3 It can be seen that the granulated lithium iron phosphate particles are in closer contact in the positive electrode sheet, and the conductive carbon black can effectively fill the pores to form a better conductive network, which can also effectively improve the rate performance; Figure 4 It can be seen that in addition to a pair of redox peaks of lithium iron phosphate in the CV graph, there are three pairs of redox peaks of lithium titanium phosphate with good symmetry at low potential, indicating that after the surface treatment of the electrode, the lithium titanium phosphate nanowires have effectively coated the surface active particles, and the lithium titanium phosphate also participates in the electrochemical reaction during the charge and discharge process, which plays a role in improving the capacity and rate performance. Figure 5 It can be seen that the fast-charging graphite has smaller grain size, lower degree of graphitization, and smaller crystal orientation than conventional graphite. Therefore, the fast-charging lithium-ion battery of the present invention has excellent rate performance, smaller volume expansion, and can prevent electrode rebound.
[0110] The fast-charge lithium-ion batteries prepared in Examples 1-3 and Comparative Examples 1-6 were placed in a cycle test cabinet for rate performance and service life tests. The results are shown in Table 1.
[0111] Table 1 Performance test results of fast-charge lithium-ion batteries of Examples 1-3 and Comparative Examples 1-6
[0112]
[0113] As can be seen from Table 1, the lithium-ion battery prepared by granulating lithium iron phosphate, surface treating the electrode with lithium titanium phosphate nanowires to prepare the positive electrode, using fast-charging graphite, high-porosity diaphragm and silicone electrolyte has a low battery impedance and excellent fast-charging capability.
[0114] From the test results of Example 1 and Comparative Example 2, it can be seen that without any of lithium titanium phosphate or lithium iron phosphate, the performance of the fast-charging lithium-ion battery obtained cannot achieve good results. This shows that lithium titanium phosphate and lithium iron phosphate have a synergistic effect in increasing the electronic conductivity of the positive electrode material and the transmission rate of lithium ions.
[0115] From the test results of Example 1 and Comparative Example 6, it can be seen that the performance of the fast-charging lithium-ion battery prepared by coating the lithium titanium phosphate nanowires and carrageenan particles at a mass ratio of 1:50 on the surface of the active layer of the electrode cannot achieve good results. This is because the preparation method of the fast-charging lithium-ion battery of the present invention uses lithium titanium phosphate nanowires to modify the surface of the electrode through a spraying process to prepare a positive electrode. By spraying lithium titanium phosphate nanowires on the surface of the electrode, the contact and coating effect between the lithium titanium phosphate and the active substance particles of the electrode surface, lithium iron phosphate, are enhanced. The lithium titanium phosphate nanowires are entangled to form a loose structure through the spraying process, which can increase the fitting effect between the positive electrode and the diaphragm, and also increase the liquid absorption and retention effect of the positive electrode, eliminate polarization, and improve the rate performance.
[0116] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0117] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0118] The present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a fast-charging lithium-ion battery, characterized in that: The steps include: Granulating lithium iron phosphate to obtain granulated lithium iron phosphate, and making the granulated lithium iron phosphate into a pole piece; Using lithium titanium phosphate nanowires to perform surface treatment on at least one side of the electrode to obtain a positive electrode; The separator, the negative electrode sheet and the positive electrode sheet are made into a winding core, the coating surface of the separator faces the positive electrode sheet, and an organic silicon electrolyte is injected into the winding core to prepare a fast-charging lithium-ion battery.
2. The preparation method according to claim 1, characterized in that The method for preparing the positive electrode sheet comprises the following steps: (1) mixing the granulated lithium iron phosphate, carbon black, PVDF and solvent in a certain weight ratio to prepare a positive electrode slurry; (2) coating, baking and rolling the positive electrode slurry in sequence to obtain a pole piece; (3) Mix lithium titanium phosphate nanowires and organic glue in a mass ratio of 1:(20-100), add the mixture into a sprayer, set the speed of the electrode plate passing through the sprayer gun to 0.8-1.5 m / min, set the spray pressure of the sprayer to 0.1-0.8 MPa, and set the spraying range to the electrode plate coating width. Perform surface treatment on the electrode plate to obtain a positive electrode plate.
3. The preparation method according to claim 2, characterized in that: The preparation method meets at least one of the following conditions: The amount of lithium iron phosphate used in the granulation is 95-99 parts, the amount of carbon black is 1-4 parts, and the amount of PVDF is 1-4 parts; The preparation method of granulated lithium iron phosphate comprises secondary sintering lithium iron phosphate particles with a particle size distribution D50 of 0.2 to 2 μm and lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm at 350 to 500° C. for 3 to 6 hours; The mass ratio of the lithium iron phosphate particles with a D50 of 0.2 to 2 μm to the lithium iron phosphate particles with a D50 of 0.02 to 0.1 μm is 1:(3 to 20); The coating method comprises coating the positive electrode slurry on the positive electrode current collector, and controlling the double-sided coating surface density to be 350-420 g / m 2 ; The organic gum is selected from at least one of gelatin, carrageenan, xanthan gum and agar.
4. The preparation method according to claim 2, characterized in that: The solvent is NMP. The preparation method of the positive electrode slurry comprises dissolving the PVDF in NMP, vacuum stirring for 3 to 6 hours, and obtaining a PVDF glue solution with a mass fraction of 3% to 8%; mixing the granulated lithium iron phosphate and carbon black for dry mixing for 0.5 to 2 hours, and then adding the PVDF glue solution, and vacuum stirring for 4 to 6 hours; finally, adding an appropriate amount of NMP according to the viscosity of the slurry, vacuum stirring for 0.5 to 1.5 hours, and then vacuum standing for defoaming for 0.5 to 2 hours to obtain the positive electrode slurry.
5. The preparation method according to claim 1, characterized in that: The method for preparing the negative electrode sheet comprises the following steps: (1) slurrying fast-charging graphite, carbon black, lithiated CMC, modified SBR and deionized water to prepare negative electrode slurry; (2) The negative electrode slurry is sequentially coated, baked, rolled, and cut to obtain a negative electrode sheet.
6. The preparation method according to claim 5, characterized in that: The preparation method meets at least one of the following conditions: The fast-filling graphite is used in an amount of 95 to 99 parts, the carbon black is used in an amount of 0.5 to 1.5 parts, the lithium CMC is used in an amount of 0.8 to 2 parts, and the modified SBR is used in an amount of 1 to 2.5 parts; The fast-filling graphite is artificial graphite with a particle size distribution D50 of 6 to 11 μm and a specific surface area of 1.3 to 4 m 2 / g, the degree of graphitization is 93.8% to 94.2%, and the OI value is 2.8 to 3.2; The coating method comprises coating the negative electrode slurry on the negative electrode current collector, and controlling the double-sided coating surface density to be 180-230 g / m 2 .
7. The preparation method according to claim 5, characterized in that: The preparation method of the negative electrode slurry comprises dissolving the lithiated CMC in deionized water, vacuum stirring for 4 to 6 hours, and obtaining a CMC glue solution with a mass fraction of 0.8% to 1.8%; mixing the fast-charging graphite and carbon black for dry mixing for 1.5 to 2.5 hours, then adding the CMC glue solution, and vacuum stirring for 3 to 6 hours; continuing to add the SBR, and vacuum stirring at a low speed for 0.5 to 1.5 hours; finally, adding deionized water according to the viscosity of the slurry, vacuum stirring for 0.5 to 1.5 hours, and then vacuum standing for defoaming for 0.5 to 2 hours to obtain the negative electrode slurry.
8. The preparation method according to claim 1, characterized in that: The diaphragm is a PTFE diaphragm with a porosity of 45% to 55%, a single-side coating of aluminum oxide and PVDF, and a thickness of 12+3 μm.
9. The preparation method according to claim 1, characterized in that: The preparation method meets at least one of the following conditions: The composition of the organosilicon electrolyte is 1.2M LiPF6 / EC:DMC, and the doping ratio of polysiloxane oligomer is 10% to 30%; The method for preparing a fast-charging lithium-ion battery also includes: subjecting the core to sequential steps of baking, hot pressing, ultrasonic welding, top and side sealing, baking, liquid injection, standing, pressure forming, aging, exhaust and secondary sealing, and capacity separation.
10. A fast-charge lithium-ion battery prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The fast-charge lithium-ion battery has a 4C constant current charging ratio of 95.0%-99.0%, a 6C constant current charging ratio of 95.0%-97.0%, an 8C constant current charging ratio of 92.0%-94.0%, and a capacity retention rate of 97%-99% after 500 6C / 1C fast-charge cycles.
Citation Information
Patent Citations
Preparation method for coating surfaces of electrodes with solid electrolyte complex liquid
CN105591105A
Lithium iron phosphate positive pole piece and preparation method and application thereof
CN113422049A
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN117558915A
Electrolyte and lithium ion battery
CN118712486A
Cited By
Binder and method for producing same, lithium iron phosphate cathode and method for producing same, lithium ion battery
CN122587634A